The Borders of the European Union in a Conflictual World
XIII, 288 p. 9 illus., 4 illus. in color.
Keywords: “This book takes a sophisticated multi-disciplinary approach to the central issue of the EU’s borders in a changing and turbulent world, and the content of the volume reflects the breadth and the significance of the problem. The focus on borders is distinctive and enables some important insights about European and world order more generally. This will be an important contribution to a growing literature on the implications of the European crisis.” - Michael Smith, Honorary Professor in European Politics, University of Warwick, UK This open access book examines the implications for the EU of a radically changed international context characterized by systemic rivalry, competition over norms and regulations, and growing strategic tension. Globalization that once tied national economies together and internationalized social phenomena, such as education, research and innovation, and tourism, has gone in reverse. An opposite trend is driving the world into distinct spheres of competing models of governance, regulation, technological development, and communication. Facing the most extensive rupture of economic and inter-state relations since the onset of the Cold War, the management of the EU’s internal and external borders is taking on a completely new meaning. The open access book brings together scholars from economics, law, and political science to provide up dated assessments and policy advice on the insecurity in the neighborhood and war in Ukraine, the EU’s role in the future European security architecture, weaponized energy dependence, and the global competition on norms. Antonina Bakardjieva Engelbrekt is Professor of European Law and Board Director of the Institute for European Law at the Faculty of Law of Stockholm University, Sweden. Per Ekman is a researcher in Political Science at the Department of Government, Uppsala University, Sweden. Anna Michalski is Associate Professor in Political Science at the Department of Government, Uppsala University, Sweden. Lars Oxelheim is Professor of International Business and Finance at University of Agder, Kristiansand, Norway, Professor Emeritus at Lund University, and affiliated with the Research Institute of Industrial Economics (IFN), Sweden.